Volcanic hazard map visualisation affects cognition and crisis decision-making. (March 2021) - Thompson Clive, Mary Anne; Lindsay, Jan Marie; Leonard, Graham Sloane; Lutteroth, Christof; Bostrom, Ann; Corballis, Paul
Abstract: Hazard maps are used to communicate complex scientific data with many audiences during volcanic unrest crises, but it is unclear how common hazard visualisation styles affect cognition, behaviour, and decision-making. Here we use eye-gaze tracking and questionnaires to explore how 81 people near a volcano in New Zealand read and make decisions with hazard maps for a hypothetical eruption. We find that greater mental effort is required to read early-stage hazard maps associated with higher uncertainty, and that showing integrated zones of low to high hazard can result in 1) higher perceived threat, 2) limited visual attention to the maps, and 3) more risk-averse decisions under pressure compared to visualising discrete hazard footprints. People with high prior risk perceptions demonstrate less attention to map content overall. The results show how map visualisation can influence cognition, decision-making, and behaviour, and have implications for crisis communication. For example, in the early stages of a volcanic event, integrated hazard zones may help capture audience attention by facilitating a high-level assessment of risk. As the event evolves, discrete footprints of individual hazard processes may help better inform high-stakes decisions for which detailed hazard knowledge is needed. Additionally, we find that providing simple tasks for the audience to carry out using the maps, and showing safe areas alongside hazardous areas, may encourage map reading. We discuss the implications of these findings, and present four evidence-based points for scientists to consider across a range of fields where hazard maps are used to communicate with non-specialist audiences. Highlights: Volcanic hazard map style affects visual attention, cognition, and decision-making. Simple tasks help guide attention to hazard maps at early, uncertain event stages. High risk perception is associated with limited visual attention to hazard maps. Integrated hazard visualisations engage early attention and high-level processing. Discrete hazard footprints encourage deliberative processing and correct inferences.